PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA) DENGAN MODERASI PERSEPSI KEADILAN (STUDI DI RSUD BENDAN KOTA PEKALONGAN) - Nugroho Adhi Pradhana, 1252020147; Utomo, Budi Sungkowo (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study was to investigate the perceptions of fairness moderate the effect of compensation on performance and job satisfaction . The specific objectives of this study is to examine and analyze whether the role of justice perceptions moderate the effect of compensation on performance and job satisfaction . Usefulness of the research is to explain and extend previous research on the effect of compensation , job satisfaction and perceptions of fairness on performance . Population and study sample was Bendan City Hospital employees pekalongan of 120 people . The research data is primary data collected directly from the respondents to the questionnaire . The research method approach with computer software SPSS for Windows version 17. The method of data analysis using Moderation Regression Analisys ( MRA ) -type quasi moderator . The results showed that perceptions of fairness weaken the influence of job satisfaction on performance , as well as perceptions of fairness does not moderate the effect of compensation on performance . Keywords : compensation , job satisfaction , perceptions of fairness , performance